Effect of Management Factor on Employee Job Satisfaction - Abatova, Assem; Říhová, Gabriela; Kronberger, Zdeněk; Vysoká škola ekonomická v Praze. Podnikohospodářská fakulta (2023)
This study aimed to examine the impact of perceived leadership styles (transformational, transactional, and laissez-faire) on employee job satisfaction in Kazakhstan. A mixed research methodology was employed, including qualitative and quantitative research methods, with 53 participants completing a questionnaire and seven semi-structured interviews conducted. The study found a statistically significant dependence between the current and preferred leadership styles of supervisors. However, there was not enough evidence to suggest a significant difference in mean values of statements evaluating job satisfaction for each perceived leadership style. The qualitative research provided insights consistent with academic literature. The findings can be useful for organizations, HR professionals and for future research.
Vedoucí práce: Gabriela Říhová
Bakalářská práce (Bc.)—Vysoká škola ekonomická v Praze. Fakulta podnikohospodářská, 2023
Obsahuje bibliografii
Textový (vysokoškolská kvalifikační práce)
Rok obhajoby 2023
Způsob přístupu: Internet
Keywords: bachelor of business administration [obor bakal. práce]; bakalářské práce; bachelor's theses